ANALISIS WACANA NOVEL SUPERNOVA : AKAR KARYA DEE LESTARI SEBUAH TINJAUAN REFERENSI - Sumanti Sumanti (Jurusan Tadris Bahasa Indonesia, 2015)
Discourse analysis can be reviewed in terms of cohesion and coherence. Cohesion includes this reference (reference), substitution (substitution), omissions (ellipsis), conjunctions (conjunction), and lexical cohesion (lexical cohesion). This study only focuses on the aspects of this reference (reference only. References there are two kinds of endofora and eksofora. Endofora subdivided into anaphora and katafora. The focus of this study is novel discourse analysis Supernova: AKAR by Dee Lestari terms of reference specifically endofora reference.